Peran Tentara Nasional Indonesia Dalam Penanganan Tindakan Terorisme Berkedok Agama - Nabila Zalfa; Irwan Triadi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
Acts of terrorism are actions that require full involvement from various security defenses of a country. Handling acts of terrorism poses a serious challenge to the security and stability of a country. Indonesia, as a country committed to protecting its citizens from the threat of terrorism, relies on the role of the Indonesian National Army (TNI) in efforts to prevent, overcome and eradicate acts of terrorism. In recent years, the threat of terrorism has increased, requiring a response from various security agencies, one of which is the TNI. The TNI plays a crucial role in efforts to deal with terrorism through a number of strategies and tactics. Article 7 paragraph 1 of Law No. 34 of 2004 explains that one of the TNI's tasks is to overcome acts of terrorism. Therefore, the TNI has the responsibility to identify potential terrorist threats. Even though there is a legal basis that regulates the role of the TNI in handling terrorism, the TNI and Polri, as well as related agencies, must work together to deal with the threat of terrorism in order to deal with this threat effectively.